Cognitive Biases Questionnaire for Psychosis (CBQp): Spanish Validation and Relationship With Cognitive Insight in Psychotic Patients - Corral, Lia; Labad, Javier; Ochoa, Susana; Cabezas, Angel; Muntané, Gerard; Valero, Joaquín; Sanchez-Gistau, Vanessa; Ahuir, Maribel; Gallardo-Pujol, David; Crosas, Josep María; Palao, Diego; Vilella, Elisabet; et al. (Frontiers in Psychiatry, 2021)
Introduction. Cognitive biases are key factors in the development and persistence of delusions in psychosis. The Cognitive Biases Questionnaire for Psychosis (CBQp) is a new self-reported questionnaire of 30 relevant situations to evaluate five types of cognitive biases in psychosis. In the context of the validation of the Spanish version of the CBQp, our objectives were to 1) analyze the factorial structure of the questionnaire with a confirmatory factor analysis (CFA); 2) relate cognitive biases with a widely used scale in the field of delusion cognitive therapies for assessing metacognition, specifically, Beck’s Cognitive Insight Scale (Beck et al, 2004); and, finally, 3) associate cognitive biases with delusional experiences, evaluated with the Peters Delusions Inventory (PDI) (Peters et al., 2017). Materials and methods. An authorized Spanish version of the CBQp, by a translation and back-translation procedure, was obtained. A sample of 171 patients with different diagnoses of psychoses was included. A confirmatory factorial analysis (CFA) was used to test three different construct models. Associations between CBQp biases, the Beck Cognitive Insight Scale (BCIS), and the Peters Delusions Inventory (PDI) were made by correlation and mean differences. Comparisons of the CBQp scores between a control group and patients with psychosis were analysed. Results. CFA showed CFI values of 0.94 and 0.95 for the models with 1, 2, and 5 factors, with RMSEA values of 0.031 and 0.029. The CBQp reliability was 0.87. Associations between cognitive biases, self-certainty and cognitive insight subscales of the BCIS were found. Similarly, associations between total punctuation, conviction, distress, and concern subscales of the PDI were also found. When compared with the group of healthy subjects, patients with psychoses scored significantly higher in several cognitive biases. Conclusion. Given the correlation between biases, a one-factor model might be more appropriate to explain the scale’s underlying construct. Biases were associated with a greater frequency of delusions, distress, conviction, and concern, as well as worse cognitive insight in patients with psychosis compared to healthy subjects.